2005
DOI: 10.1016/j.molcel.2005.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for the Recognition of Phosphorylated and Phosphoacetylated Histone H3 by 14-3-3

Abstract: Phosphorylation of histone H3 is implicated in transcriptional activation and chromosome condensation, but its immediate molecular function has remained obscure. By affinity chromatography of nuclear extracts against modified H3 tail peptides, we identified 14-3-3 isoforms as proteins that bind these tails in a strictly phosphorylation-dependent manner. Acetylation of lysines 9 and 14 does not impede 14-3-3 binding to serine 10-phosphorylated H3 tails. In vivo, 14-3-3 is inducibly recruited to c-fos and c-jun … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
197
3
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(215 citation statements)
references
References 61 publications
(76 reference statements)
12
197
3
3
Order By: Relevance
“…Pull-downs with H3S28ph showed higher enrichments of 14-3-3 proteins than H3S10ph, which is consistent with previous reports. 12 −14 None of the phosphorylated threonine residues mediated binding of the 14-3-3 proteins, although 14-3-3 proteins are known to bind such phosphorylation sites as well. The second amino acid downstream of the phosphorylation site (P + 2) is critical in most 14-3-3 binding sites, and Figure 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Pull-downs with H3S28ph showed higher enrichments of 14-3-3 proteins than H3S10ph, which is consistent with previous reports. 12 −14 None of the phosphorylated threonine residues mediated binding of the 14-3-3 proteins, although 14-3-3 proteins are known to bind such phosphorylation sites as well. The second amino acid downstream of the phosphorylation site (P + 2) is critical in most 14-3-3 binding sites, and Figure 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This modification is recognized by the 14-3-3ζ protein, a member of the 14-3-3 protein family [76]. Furthermore, studies in Drosophila melanogaster have indicated that this protein family is involved in recruiting components of the elongation complex to chromatin [77].…”
Section: Regulating the Binding Of Chromatin Factorsmentioning
confidence: 99%
“…6(G)]. 72 The jumonji domain of JHDM3A (JMJD2A) catalyzes the demethylation of di-and tri-methylated Lys10 and Lys 37 in histone H3 [ Fig. 6(H)].…”
Section: Examination Of the Morfs In Rnap II And Histone H3mentioning
confidence: 99%